ENT600 Smart Jacket / Ku Nazirah Ku Aziz ... [et al.] - Ku Aziz, Ku Nazirah; Mior Ahmad Faizal, Mior Afiq Hilmi; Hasim, Fatin Syahirah; Moden, Abdul Niat; Shukri, Siti Natasha (2019)
The product to be developed is a Smart Jacket. It is commonly observed that most of the citizen wearing jacket for wherever they go. Current weather which are unstable as sometimes it goes with hot Sunny days or heavily cold rain. This lead to inconvenience to the citizen as they start practicing on using public transportation. Thus, the team is developing Smart Jacket, a wearing jacket that convenience for who are wearing Smart Jacket during out of their home.